Tailoring the interaction between graphene oxide and antibacterial pyridinium salts by terminal functional groups. (30th April 2020) - Fujii, R.; Okubo, K.; Takashiba, S.; Bianco, A.; Nishina, Y.
Abstract: Nanocarbons, especially two-dimensional carbons, have received considerable attention due to their unique structure and physical and chemical properties, which make them promising candidate materials for biomedical applications. In this study, we focus on graphene oxide (GO), which has many oxygenated functional groups and high affinity with water and biomaterials, and the synthesis of GO complexes with antibacterial agents, like cetylpyridinium chloride (CPC) and its derivatives. We found that the sustained release of CPCs from GO can be controlled by changing the terminal functional group of CPC. The prepared GO-CPC complexes were subjected to antibacterial tests against S. mutans . CPC with the carboxy group was degraded by the oxidizing property of GO, resulting in the loss of antibacterial properties. On the other hand, the other CPC derivatives were released from GO and showed antibacterial activities. Finally, we propose a new mechanism describing how GO and CPC form a functional complex, and how CPC is released from this complex. These findings will lead to pioneering the carbon-based functional antibacterial agents designed at the molecular level. Graphical abstract: Image 1